2005
DOI: 10.1021/jo050644v
|View full text |Cite
|
Sign up to set email alerts
|

Silatropic Carbonyl Ene Cyclizations in the Synthesis of Pseudosugars and Hydroxylated Piperidines

Abstract: [reaction: see text] We describe two applications of silicon-tethered thermal allyl transfer reactions of alpha-silyloxyaldehydes; formally, these processes can be regarded as silatropic carbonyl ene reactions in which the silicon tether is transferred to the aldehyde oxygen concurrent with carbonyl allylation. In the first application, isoserinal substrates, which bear side-chain nitrogen functionality, are elaborated to dihydroxypiperidines. In the second application, a product of cyclohexadienyl transfer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A preliminary attempt at the stereoselective dioxygenation of 6 employed a singlet oxygen cycloaddition as a method to establish the required functional group pattern 11. While this transformation occurred in acceptable yield, the complete lack of stereocontrol in this reaction (1:1 diastereomer ratio) suggested that other methods for this dioxygenation would be required 12…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary attempt at the stereoselective dioxygenation of 6 employed a singlet oxygen cycloaddition as a method to establish the required functional group pattern 11. While this transformation occurred in acceptable yield, the complete lack of stereocontrol in this reaction (1:1 diastereomer ratio) suggested that other methods for this dioxygenation would be required 12…”
Section: Methodsmentioning
confidence: 99%
“…1 This silatropic carbonyl ene cyclisation was found to be stereospecific and highly stereoselective, and we reported its application to the stereocontrolled synthesis of carbasugars and hydroxylated piperidines. 2 Mechanistically, we view this allylic transfer to occur in concert with Si-O bond formation as depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…J 14.5, 2-H eq ),2.06 (1 H, ddd, J 14.5, 5 8,. 2.0, 2-H ax ), 3.43 (1 H, s, 4-H), 3.65 (1 H, d, J 5.8, 3-H), 3.73 (1 H, t, J 6.8, 6-H), 4.20 (1 H, dd, J 6.8, 1.2, 6-H ), 4.44 (1 H, d, J 12.1) and 4.54 (1 H, d, J 12.1, CH 2 Ph), 4.57 (1 H, d, J 12.2, CHHPh), 4.58 (1 H, d, J 6.8, 5-H), 4.62 (1 H, d, J 12.2, CHH Ph), 5.59 (1 H, s, 1-H), 7.28-7.40 (10 H, m, 2 × Ph); d C (100 MHz; CDCl 3 ) 33.0 (t), 64.7 (t), 71.1 (t), 71.2 (t), 72.3 (d), 73.9 (d), 77.2 (d), 99.9 (d), 127.5-128.5 (overlapping), 138.2 (2 × s); m/z (ESI + ) 349 (MNa + , 100%).…”
mentioning
confidence: 99%
“…[11] While this transformation occurred in acceptable yield, the complete lack of stereocontrol in this reaction (1:1 diastereomer ratio) suggested that other methods for this dioxygenation would be required. [12] Recent studies in our laboratory have focused on the development of a platinum-catalyzed enantioselective 1,4-diboration of 1,3-dienes as a method for 1,4-dioxygenation of these substrates. [13] In a related vein, we considered that a diastereoselective version of this reaction might be useful for the elaboration of complex diene substrates and enable the synthesis of the highly hydroxylated core of the isocarbostyrils such as 1-5.…”
mentioning
confidence: 99%